THU0253 Triple positivity to antiphospholipid antibodies in primary antiphospholipid syndrome: increased risk of arterial thromboses and abortions. (15th June 2017) - Signorelli, F; Balbi, G; Levy, RA
Abstract : Background: Triple positivity (TP) to antiphospholipid antibodies (aPL) has been associated with increased risk of thrombotic and gestational events in different populations of antiphospholipid syndrome (APS) patients. Nonetheless, the majority of the studies evolved APS secondary to systemic lupus erythematosus (SLE). Objectives: To investigate whether TP increases the risk of criteria and non-criteria manifestations in primary APS (pAPS) patients. Methods: A cross-sectional study was performed in a group of 74 outpatients who fulfilled APS classification criteria (Sydney; N=67) or with thrombocytopenia and persistent circulating aPL, but no criteria manifestations of APS (N=7), seen in our department. Clinical and serological features collected during medical examination and by chart review were correlated to the presence or not of aPL TP. Results: Nineteen out of 74 pAPS patients had aPL TP (25.7%). Demographic and clinical characteristics are shown in Table 1 . In a bivariate analysis, TP was associated with the presence of combined thrombotic and obstetric manifestations (p=0.008), three or more abortions (abortion 3+; p=0.043), and livedo (p=0.023). In a multivariate regression analysis, the model was adjusted to age, sex, race and variables with p<0.10 in the bivariate analysis (arterial thrombosis, abortion 3+, livedo, thrombocytopenia, and thrombotic+obstetric). After the analysis, arterial thrombosis (OR 5.74; CI95% 1.31–25.05; p=0.02) and abortion 3+ (OR 12.55; CI95% 1.01–156.54; p=0.049) were associated with TP. Conclusions: In our cohort of primary APS patients, triple positivity was associated with arterial thromboses and the occurrence of 3 or more abortions, with increased risk over 5 and 12 folds, respectively. Disclosure of Interest: None declared